Co-solving groundwater depletion and seasonal flooding through an innovative managed aquifer recharge approach: converting pilot to a regional solution in the Ram Ganga Sub-basin - Gangopadhyay, Prasun K.; Sharma, Bharat R.; Pavelic, Paul (2018)
Climate induced extreme events such as floods and droughts are often disastrous in incidences and affects Indian economy often. Low per capita surface water storage (225 m3/capita1), few sites for additional storages facilities and depleting groundwater aquifers reduce the resilience of the communities to alleviate the day-to-day short age and larger seasonal shocks. India has a long history of storing and recharging runoff waters through community participation. Ongoing such programs are focused on drought-prone or socio-economically weak areas and exclude the flood prone zones. The present study aims to improve the groundwater resources availability through diverting flows from rivers or canals at times when these flows pose flood risk and recharging the groundwater through suitable artificial recharge structures. This method addresses the issue of groundwater depletion as well as reducing the flood risks. A geo-hydrological analysis in spatial platform using data available in public domain and detailed ground survey, a site was identified in Jiwai Jadid village of Milk Block of Rampur district of Uttar Pradesh, India. A community owned pond was retrofitted with recharge wells and associated infrastructure to draw excess monsoon water from a nearby flood-prone river. The preliminary results show a positive impact on groundwater table and water quality. However, to achieve the full benefit of the method it is required to implement it in larger scale. Ongoing government programs that are focused on livelihood improvement and natural resources management are the best options to scale up such effect in regional scale.